Infested Shoot Clipping for Managing Brinjal Shoot and Fruit Borer: An Eco-Friendly Approach (Research in Agriculture Livestock and Fisheries, 2025)
The brinjal shoot and fruit borer (BSFB) is a noteworthy hindrance that harshly affects brinjal production. However, effective control of the insect enables growers to get the maximum return. The present investigation was carried out to evaluate the effectiveness of infested fruit clipping as an eco-friendly approach to minimize BSFB infestation and enhance marketable yield at the Entomology Research Field, Department of Entomology, Bangladesh Agricultural University, Mymensingh during the Rabi season. Shoot Clipping provided moderate protection to Brinjal fruit against the infestation of BSFB.  However, shoot clipping with sanitation provided sufficient protection to brinjal fruit against BSFB. The result also demonstrated that each of the treatment plots produced significantly better yields compared to the control. The lowest yield was produced in the untreated control, which was less than 6 t/ha. The highest brinjal was produced at Shoot Clipping + Sanitation, with the mean yield more than 14t/ha. Shoot clipping treated plot production was 10 t/ha. The overall results suggested that shoot clipping with sanitation provided the maximum marketable yield of brinjal. The benefit-cost ratio (BCR) was higher in the plot treated with shoot clipping with sanitation, which was 1.68. Thus, shoot clipping with sanitation could be a valuable IPM module for better management of BSFB.Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 259-273